COMPOUNDING:CLASSIFICATION OF COMPOUNDS, THEIR STRUCTURAL AND SEMANTIC FEATURES - Khaydarova Nigora; Fayziddinova Munisa (TADQIQOTLAR, 2025)
Abstract This article explores the process of compounding as a productive method of word-formation in the English language. It presents a detailed classification of compound words based on their structural and semantic features, highlighting distinctions between closed, hyphenated, and open compounds, as well as between endocentric, exocentric, copulative, and appositional types. The paper also analyzes the grammatical behavior, stress patterns, and syntactic roles of compounds in modern English. The study emphasizes the importance of compounding in vocabulary expansion and reflects on its growing role in adapting language to cultural and technological change.